# How do you write the inverse variation equation of the following. Y varies inversely with x and y = -12 when x = 6?

The inverse variation equation is y = k/x, where k is the constant of variation. To find the value of k, we can substitute the given values of y and x into the equation. Therefore, -12 = k/6. Solving for k, we get k = -72. Thus, the inverse variation equation is y = -72/x.

By signing up, you agree to our Terms of Service and Privacy Policy

Inverse variation equation is

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7